Diversité Et Variabilité Du Régime Alimentaire Des Éléphants Du Parc National d’Azagny (Sud - Côte d’Ivoire) - Kouame Djaha; Gone Bi Zoro Bertin; Kpangui Kouassi Bruno; Koffi Bene Jean Claude; Koffi Kouao Jean; Vroh Bi Tra Aimé; Adou Yao Constant Yves (European Scientific Journal, ESJ, 2017)
In Côte d'Ivoire, Azagny National Park has a small forest elephants population, described as isolated, self-contained and whose survival depends on the diversity of local biological resources. A study was undertaken to assess the diversity of the plant species consumed and the feeding preference of this large mammal. Pedestrian surveys were carried out in the different biotopes traveled by the elephants during one year, in search of fresh and old traces of nutrition and droppings. As a result of these inventories, six organs of 282 plant species have been identified has consumed by elephant. In this plant species list, three families are the most represented: the Apocynaceae, the Euphorbiaceae and the Rubiaceae. Among the elephant diet, five species appear to be the most consumed: Aframomum melegueta (1.45%), Aframomum sceptrum (1.45%), Sacoglottis gabonensis (1.27%), Echinochloa pyramidalis (1.2%) and Albizia adianthifolia (1.2%). Considering the number and type of organs harvested from plants, the study reveals that they varied from one species to another well. In general, leaves (256 species 90.8%) and fruits (95 species or 33.7%) have emerged as the most consumed organs of elephants. In view of this diet importance in elephant survival in the park, it would be important to identify the type of species consumed seasonally and to assess their availability in each of the biotopes traveled.